Molecular analysis of pericentrin gene (PCNT) in a series of 24 Seckel/microcephalic osteodysplastic primordial dwarfism type II (MOPD II) families. Issue 12 (29th July 2009) - Willems, M; Geneviève, D; Borck, G; Baumann, C; Baujat, G; Bieth, E; Edery, P; Farra, C; Gerard, M; Héron, D; Leheup, B; Le Merrer, M; et al.
Abstract : Microcephalic osteodysplastic primordial dwarfism type II (MOPD II, MIM 210720) and Seckel syndrome (SCKL, MIM 210600) belong to the primordial dwarfism group characterised by intrauterine growth retardation, severe proportionate short stature, and pronounced microcephaly. MOPD II is distinct from SCKL by more severe growth retardation, radiological abnormalities, and absent or mild mental retardation. Seckel syndrome is associated with defective ATR dependent DNA damage signalling. In 2008, loss-of-function mutations in the pericentrin gene ( PCNT ) have been identified in 28 patients, including 3 SCKL and 25 MOPDII cases. This gene encodes a centrosomal protein which plays a key role in the organisation of mitotic spindles. The aim of this study was to analyse PCNT in a large series of SCKL-MOPD II cases to further define the clinical spectrum associated with PCNT mutations. Among 18 consanguineous families (13 SCKL and 5 MOPDII) and 6 isolated cases (3 SCKL and 3 MOPD II), 13 distinct mutations were identified in 5/16 SCKL and 8/8 MOPDII including five stop mutations, five frameshift mutations, two splice site mutations, and one apparent missense mutation affecting the last base of exon 19. Moreover, we demonstrated that this latter mutation leads to an abnormal splicing with a predicted premature termination of translation. The clinical analysis of the 5 SCKL cases with PCNT mutations showed that they all presented minor skeletal changes and clinical features compatible with MOPDII diagnosis. It is therefore concluded that, despite variable severity, MOPDII is a genetically homogeneous condition due to loss-of-function of pericentrin.